KUALITAS PELAYANAN DI PT. EKSIS TOUR AND TRAVEL PEKANBARU - Parma.S., Sebastian Beinal; Yusrizal, Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The tourism industry is one of the largest foreign exchange earners for the country, contributing significantly to national economic growth. Travel agents are one of the services that assist tourists in planning and executing their trips to desired destinations. One of the travel agents in Pekanbaru is PT. Eksis Tour and Travel. The quality of service at this travel agency will be the main focus of this study. This study aims to determine the quality of service at PT. Eksis Tour and Travel Pekanbaru. This study uses a quantitative method with a descriptive approach, and data is obtained through a survey of customers who have used the services of PT. Eksis Tour and Travel Pekanbaru using a questionnaire based on several points related to service quality, namely: Tangible (tangible), Empathy (empathy), Reliability (reliability), Responsiveness (responsiveness), and Assurance (assurance). The results of the study indicate that the majority of respondents in terms of service quality at PT. Eksis Tour and Travel Pekanbaru are in the satisfied category, with the sub-variable Assurance (guarantee) having the highest score among the other sub-variables, achieving customer satisfaction of 80%, and the indicator with the highest score being the guarantee of customer data security. Keywords: Tourism, Service Quality, Travel Agent, PT. Eksis Tour and Travel.